2007
DOI: 10.1002/anie.200701868
|View full text |Cite
|
Sign up to set email alerts
|

Heck‐Type Cyclization of Oxime Ethers: Stereoselective Carbon–Carbon Bond Formation with Aryl Halides To Produce Heterocyclic Oximes

Abstract: Die Benzhydrylgruppe ist der Schlüssel: Die effiziente Alkylierung 3‐substituierter Aziridin‐2‐carboxylate gelingt nur bei N‐Benzhydryl‐geschützten Aziridinen, und sie verläuft mit vollständiger Retention der Konfiguration an der 2‐Position. Sequenzielle katalytische asymmetrische Aziridinierung und Aziridinalkylierung wurden für die Synthese von BIRT‐377 (siehe Formel) eingesetzt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…The ( Z )‐product from the Heck pathway is not in agreement with the experimental result, which gave the ( E )‐product. Although there is a possibility of pyramidal inversion of palladium amide nitrogen on D to eventually deliver the ( E )‐product, there is no obvious driving force, such as steric factors, for this inversion to occur 18b. In addition, the rate‐limiting step of this reaction is inconsistent with that of the Heck pathway, in which the CH cleavage step, β‐hydride elimination, is usually not rate limiting 19…”
Section: Methodsmentioning
confidence: 99%
“…The ( Z )‐product from the Heck pathway is not in agreement with the experimental result, which gave the ( E )‐product. Although there is a possibility of pyramidal inversion of palladium amide nitrogen on D to eventually deliver the ( E )‐product, there is no obvious driving force, such as steric factors, for this inversion to occur 18b. In addition, the rate‐limiting step of this reaction is inconsistent with that of the Heck pathway, in which the CH cleavage step, β‐hydride elimination, is usually not rate limiting 19…”
Section: Methodsmentioning
confidence: 99%
“…Taking a lead from this work, in 2007, Ohno et al [73] reported a very important breakthrough in the Heck-Mizoroki coupling of aryl halides with oxime ethers (Figure 1.18). The reaction could be performed under two types of conditions, one using NaOtBu in m-xylene at 135 ∘ C (Method A) and the other K 2 CO 3 in diglyme at 160 ∘ C. For convenient analysis, the ketimine intermediate was converted via acid hydrolysis to the ketone product.…”
Section: Siet 3 Armentioning
confidence: 99%
“…The Heck-Mizoroki-type reaction on N-pyrazyl imines using Rh(I) as described by Ishiyama and Hartwig[71] 18. Heck-Mizoroki-type cyclization of oxime ethers as reported by Ohno et al[73].…”
mentioning
confidence: 99%
“…If the allylamides are replaced by the O-benzylated oxime 55 during the intramolecular Heck reaction it is possible to obtain a γ-carboline derivative containing only an exocyclic double bond with the (E) and (Z) isomers in a ratio of 30:70 [109]. …”
Section: Syntheses With the Formation Of The C(4)-c(4a) Bondmentioning
confidence: 99%